Reduced Spinal Cord Movement With the Straight Leg Raise Test in Patients With Lumbar Intervertebral Disc Herniation. Issue 15 (1st August 2017) - Rade, Marinko; Pesonen, Janne; Könönen, Mervi; Marttila, Jarkko; Shacklock, Michael; Vanninen, Ritva; Kankaanpää, Markku; Airaksinen, Olavi
Abstract : Study Design: Controlled radiological study. Objective: To explore whether impairment of neural excursion during the straight leg raise test occurs in patients with sciatic symptoms secondary to lumbar intervertebral disc herniation (LIDH). Summary of Background Data: Earlier studies have shown that during the straight leg raise (SLR) test in asymptomatic volunteers tensile forces are consistently transmitted throughout the neural system and the thoracolumbar spinal cord slides distally. Methods: Fifteen patients with sciatic symptoms due to subacute LIDH were studied with a 1.5 T magnetic resonance scanner. First, a spine specialist diagnosed the LIDH using conventional scanning sequences. Following this subjects were scanned using different scanning sequences for planning and measurement purposes. Displacement of the conus medullaris during the unilateral and bilateral SLR was quantified reliably with a randomized procedure and compared between manoeuvres. Results: The results showed 66.6% less excursion of conus medullaris with SLR performed on the symptomatic side compared with excursions measured with SLR performed on the asymptomatic side ( p ⩽ 0.001). Conclusion: In patients with LIDH, the neural displacement on the symptomatic side is significantly reduced by the compressing IVD herniation. To our knowledge, these are the first data in intact human subjects to support the limitation of neural movements in the vertebral canal with LIDH. Level of Evidence: 3